2014
DOI: 10.1177/0149206314560411
|View full text |Cite
|
Sign up to set email alerts
|

When Is Empowerment Effective? The Role of Leader-Leader Exchange in Empowering Leadership, Cynicism, and Time Theft

Abstract: Applying arguments from social exchange theory, we theoretically derive and empirically test a multilevel model that informs theory on leadership, cynicism, and deviant withdrawal. Namely, we examine the moderating effect of the upward exchange relationship of a leader on empowering leadership behaviors as they affect subordinate psychological empowerment, cynicism, and time theft. In a sample of 161 employees across 37 direct supervisors, empowering leadership was associated with reduced employee cynicism bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
164
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(191 citation statements)
references
References 93 publications
6
164
0
8
Order By: Relevance
“…Cynics may feel that hiding knowledge can harm the progress of the perpetrators and the organization and that leaving the job can be a way of escaping the ordeals of incivilities in their workplace. In line with our findings, research has shown that cynics reciprocate frustrating experiences by withdrawing in minor, yet impactful and deviant, ways in efforts to balance their exchange with the organization (Abubakar et al., ; Cortina et al., ; Lorinkova & Perry, ).…”
Section: Discussionsupporting
confidence: 91%
“…Cynics may feel that hiding knowledge can harm the progress of the perpetrators and the organization and that leaving the job can be a way of escaping the ordeals of incivilities in their workplace. In line with our findings, research has shown that cynics reciprocate frustrating experiences by withdrawing in minor, yet impactful and deviant, ways in efforts to balance their exchange with the organization (Abubakar et al., ; Cortina et al., ; Lorinkova & Perry, ).…”
Section: Discussionsupporting
confidence: 91%
“…Together, empowering leadership and the increasingly flat structure of organisations allow more autonomy and facilitate the flow of communication. In line with this, various desirable outcomes of empowering leadership, such as job satisfaction, employee performance, creativity, and extra‐role behaviours, have been identified in previous empirical studies (Amundsen & Martinsen, ; Auh, Menguc, & Jung, ; Lorinkova & Perry, ; Srivastava, Bartol, & Locke, ; Zhang & Bartol, ).…”
Section: Introductionsupporting
confidence: 68%
“…Empowering leadership is a leadership style in which leaders share power by encouraging subordinates to express their ideas. This enhances subordinates' autonomy and investment in their work and also involves subordinates in decision‐making, information sharing, and teamwork (Chen et al, ; Chen et al, ; Lorinkova & Perry, ). Previous work has suggested that empowering leadership increases subordinates' intrinsic motivation (Zhang & Bartol, ).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…tation (MacLean, Litzky, & Holderness, 2015;Palanski & Yammarino, 2011), and that broken promises lead to distrust, anger, and cynicism (Chiaburu, Peng, Oh, Banks, & Lomeli, 2013;Lorinkova & Perry, 2014). Taken together, we expect that a gender diversity mixed message will negatively influence the perceived behavioral integrity of an organization and in turn its attractiveness.…”
Section: Study Background and Hypothesesmentioning
confidence: 96%